2021
DOI: 10.1155/2021/6550388
|View full text |Cite
|
Sign up to set email alerts
|

TAB2 Promotes the Stemness and Biological Functions of Cervical Squamous Cell Carcinoma Cells

Abstract: Cancer stem cells are a key population participating in the promotion of the cervical cancer progression through interacting with cancer cells. Existing studies have preliminary revealed that cervical cancer stem cells contribute to tumor recurrence and chemotherapy resistance. However, the specific mechanisms involved in regulating cell functions remain largely unknown. Here, we analyzed published data from public databases and our global transcriptome data, thus identifying cancer-related signaling pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The knockdown of the TAB2 gene significantly inhibits cell proliferation and induces cell apoptosis. www.nature.com/scientificreports/ Moreover, the regulatory mechanism of TAB2 in cancer stem cells (CSCs) is related to promoting the malignant transformation and invasiveness of CC, which is a prognostic marker of CC 52 . Our results are consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of the TAB2 gene significantly inhibits cell proliferation and induces cell apoptosis. www.nature.com/scientificreports/ Moreover, the regulatory mechanism of TAB2 in cancer stem cells (CSCs) is related to promoting the malignant transformation and invasiveness of CC, which is a prognostic marker of CC 52 . Our results are consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-142-3p targets the 3’UTR of TAB2 mRNA, and the knockout of TAB2 was associated with granulocytic differentiation [ 36 ]. Notably, TAB2 has been shown to be a major activator of the NF-κB pathway and the maintenance of cancer stem cell-like properties in cervical squamous cell carcinoma cells [ 213 ]. Reduced miR-142-3p levels, as Wang et al demonstrated among AML patients, can therefore contribute to APL development by relieving its inhibition of CCNT2 and TAB2 targets [ 36 , 207 ].…”
Section: The Role Of Mir-142 In Hematological Malignanciesmentioning
confidence: 99%